2023
DOI: 10.3390/nano13202744
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Vacancy-Ordered Double Perovskite Halides A2Sn1−xTixY6 (A = K, Rb, Cs; Y = Cl, Br, I): Promising Materials for Photovoltaic Applications

Wen Chen,
Gang Liu,
Chao Dong
et al.

Abstract: In the present study, the structural, mechanical, electronic and optical properties of all-inorganic vacancy-ordered double perovskites A2Sn1−xTixY6 (A = K, Rb, Cs; Y = Cl, Br, I) are explored by density functional theory. The structural and thermodynamic stabilities are confirmed by the tolerance factor and negative formation energy. Moreover, by doping Ti ions into vacancy-ordered double perovskite A2SnY6, the effect of Ti doping on the electronic and optical properties was investigated in detail. Then, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Dong et al reported on the geometrical, electronic, and optical properties of double-perovskite material Cs 2 NaMX 6 (M = In, Tl, Sb, Bi; X = Cl, Br, I) using the first-principles calculations to investigate the halogen anions and metal anions affecting the properties [ 26 ]. The structural, opto-electronic, and mechanical properties of all-inorganic vacancy-ordered double-perovskite A 2 Sn 1−x Ti x Y 6 (A = K, Rb, Cs; Y = Cl, Br, I) were investigated using DFT, as reported by Chen et al [ 27 ]. The band structure and optical absorption results demonstrated that all A 2 Sn 1−x Ti x Br 6 (A = K, Rb, Cs) materials are semiconductors with band gaps between 0.9–1.6 eV, and A 2 TiBr 6 (A = K, Rb, Cs) compounds have the highest optical absorption both in the visible and ultraviolet regions, making them excellent materials for photovoltaic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al reported on the geometrical, electronic, and optical properties of double-perovskite material Cs 2 NaMX 6 (M = In, Tl, Sb, Bi; X = Cl, Br, I) using the first-principles calculations to investigate the halogen anions and metal anions affecting the properties [ 26 ]. The structural, opto-electronic, and mechanical properties of all-inorganic vacancy-ordered double-perovskite A 2 Sn 1−x Ti x Y 6 (A = K, Rb, Cs; Y = Cl, Br, I) were investigated using DFT, as reported by Chen et al [ 27 ]. The band structure and optical absorption results demonstrated that all A 2 Sn 1−x Ti x Br 6 (A = K, Rb, Cs) materials are semiconductors with band gaps between 0.9–1.6 eV, and A 2 TiBr 6 (A = K, Rb, Cs) compounds have the highest optical absorption both in the visible and ultraviolet regions, making them excellent materials for photovoltaic applications.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the latest developments and challenges and the future trends in nano-optics and nano-optoelectronics, this Special Issue compiles sixteen papers dedicated to very recent advances in nanostructures and nanomaterials. In these papers, novel nanostructures and nanomaterials, such as metastructures [ 1 , 2 , 3 ], metalenses [ 4 , 5 ], nanoparticles [ 6 , 7 ], layered 2D materials [ 8 , 9 ], and nano-semiconductors [ 10 , 11 ], are presented in detail. Due to their exceptional properties, these nanostructures/nanomaterials offer a diverse range of novel applications in photodetectors [ 1 , 9 , 11 ], solar cells [ 2 , 9 , 10 ], modulators [ 1 , 3 , 8 ], light emitters [ 1 , 7 ], optoelectronic integration [ 5 , 6 ], super-resolved imaging [ 4 , 5 ], nanofabrication [ 4 ], etc.…”
mentioning
confidence: 99%
“…In these papers, novel nanostructures and nanomaterials, such as metastructures [ 1 , 2 , 3 ], metalenses [ 4 , 5 ], nanoparticles [ 6 , 7 ], layered 2D materials [ 8 , 9 ], and nano-semiconductors [ 10 , 11 ], are presented in detail. Due to their exceptional properties, these nanostructures/nanomaterials offer a diverse range of novel applications in photodetectors [ 1 , 9 , 11 ], solar cells [ 2 , 9 , 10 ], modulators [ 1 , 3 , 8 ], light emitters [ 1 , 7 ], optoelectronic integration [ 5 , 6 ], super-resolved imaging [ 4 , 5 ], nanofabrication [ 4 ], etc. This Special Issue also encompasses the latest advancements in practical nano-optical and nano-optoelectronic technologies, such as femtosecond laser nano-processing [ 12 ], atomic layer coating [ 13 ], and new designs for photonic integration engineering [ 14 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation